2005
DOI: 10.1111/j.1365-294x.2005.02543.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of population genetic structure in Athyrium distentifolium (Pteridophyta) using AFLPs and SSRs from anonymous and transcribed gene regions

Abstract: To examine the performance and information content of different marker systems, comparative assessment of population genetic diversity was undertaken in nine populations of Athyrium distentifolium using nine genomic and 10 expressed sequence tag (EST) microsatellite (SSR) loci, and 265 amplified fragment length polymorphism (AFLP) loci from two primer combinations. In range-wide comparisons (European vs. North American populations), the EST-SSR loci showed more reliable amplification and produced more easily s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 66 publications
15
104
0
1
Order By: Relevance
“…So far, only a few, mostly regional studies have included direct comparison between AFLP and microsatellite variation. The results suggest that AFLPs may reveal more structure in large data sets than microsatellites (Gaudeul et al, 2004;Woodhead et al, 2005;S nsteb et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…So far, only a few, mostly regional studies have included direct comparison between AFLP and microsatellite variation. The results suggest that AFLPs may reveal more structure in large data sets than microsatellites (Gaudeul et al, 2004;Woodhead et al, 2005;S nsteb et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Thus, for large-scale intraspecific studies and for interspecific studies, AFLP may be more appropriate as molecular marker (cf. Mariette et al, 2001;Gaudeul et al, 2004;Woodhead et al, 2005;S nsteb et al, 2007).…”
Section: Aflps Versus Microsatellitesmentioning
confidence: 99%
“…This bridges the gap with the widely used candidate gene approach to functional genetics. Thirdly, the regions in which primers are designed are likely to be conserved between species, reducing the probability of null alleles, and making crossamplification and direct comparisons between species a viable option (Woodhead et al, 2005).…”
Section: How Can Ngs Technologies Help Us To Get Around These Limitatmentioning
confidence: 99%
“…In addition to concerns about selection, we anticipate that EST markers are less likely to be polymorphic than anonymous markers owing to functional constraints in transcribed regions, and may contain less informative differences between the hybridizing taxa (Ellis and Burke, 2007). Woodhead et al (2005) compared genetic diversity in the fern Athyrium distentifolium using EST-SSRs, genomic SSRs and AFLPs, and all marker types showed similar rank orders of population diversity and comparable F ST values, suggesting polymorphism in EST-SSRs can often be considered effectively neutral. In a comparison of EST-SSRs and genomic SSRs in Castanea, Martin et al (2010) found no significant differences in the F ST values calculated with the two marker types, suggesting no deviation from selective neutrality.…”
Section: How Can Ngs Technologies Help Us To Get Around These Limitatmentioning
confidence: 99%
“…For example, a potentially large number of microsatellites could be developed inexpensively through mining D. v. virgifera expressed sequence tag (EST) databases (Kim et al 2008). Although EST-derived microsatellites loci are part of an expressed gene and thus may be subject to direct selection, background selection, or genetic hitchhiking (Li et al 2002), polymorphisms in EST-derived microsatellites often behave as effectively neutral markers and can provide valid information about the genetic structure of natural populations (Woodhead et al 2005, Kim et al 2008.…”
Section: Discussionmentioning
confidence: 99%